2022
DOI: 10.1007/s40256-022-00559-0
|View full text |Cite
|
Sign up to set email alerts
|

Very Short Versus Longer Dual Antiplatelet Treatment After Coronary Interventions: A Systematic Review and Meta-analysis

Abstract: Background Very short (≤ 3 months) duration of dual antiplatelet therapy (VSDAPT) has recently been proposed after percutaneous coronary intervention (PCI) with drug-eluting stent (DES). Objectives The aim of this systematic review and meta-analysis was to compare very short versus > 3 months' duration of dual antiplatelet treatment (DAPT) in patients undergoing PCI with DES, focusing on ischemic and bleeding events. Methods Three major databases (Medline, Cochrane Central Register of Controlled Trials, and Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The previous results were confirmed by another meta-analysis, which included studies with a previous generation of stents [ 32 ]. Recently, the results of our meta-analysis focusing on odds of NACEs found that DAPT shorter than three months significantly decreased the NACEs by 17% and the severe bleedings by 29% without increasing ischemic events [ 33 ]. Moreover, the trial sequential analysis showed that it was not under-powered and the results could be applied safely.…”
Section: Discussionmentioning
confidence: 99%
“…The previous results were confirmed by another meta-analysis, which included studies with a previous generation of stents [ 32 ]. Recently, the results of our meta-analysis focusing on odds of NACEs found that DAPT shorter than three months significantly decreased the NACEs by 17% and the severe bleedings by 29% without increasing ischemic events [ 33 ]. Moreover, the trial sequential analysis showed that it was not under-powered and the results could be applied safely.…”
Section: Discussionmentioning
confidence: 99%
“…Although short duration or de-escalated DAPT strategy might reduce bleeding without increasing cardiovascular events in some studies, but current guideline still recommend DAPT consisting of a potent P2Y12 receptor inhibitor in addition to aspirin for 12 months in acute coronary syndrome patients after PCI, irrespective of the stent type, unless there are contraindications adequate ( 36 38 ). Studies are deserved to evaluate the effiicacy and safety of short duration DAPT in elder population.…”
Section: Discussionmentioning
confidence: 99%
“…An active area of research is to find the ideal duration and combination of DAPT regimens. Several studies have been conducted to evaluate different regimens and their efficacy and safety profiles [ 51 , 52 ]. A meta-analysis by Tsigkas et al, comparing the use of a concise (less than three months) duration of DAPT to a longer duration (more than three months) in patients undergoing PCI with DES, was conducted.…”
Section: Reviewmentioning
confidence: 99%